The Glycosylphosphatidylinositol-Anchored Variable Region of Llama Heavy Chain-Only Antibody JM4 Efficiently Blocks both Cell-Free and T Cell-T Cell Transmission of Human Immunodeficiency Virus Type 1 - Liu, Lihong (J Virol, 2016)
The variable regions (VHHs) of two heavy chain-only antibodies, JM2 and JM4, from llamas that have been immunized with a trimeric gp140 bound to a CD4 mimic have been recently isolated (here referred to as VHH JM2 and VHH JM4, respectively). JM2 binds the CD4-binding site of gp120 and neutralizes HIV-1 strains from subtypes B, C, and G. JM4 binds gp120 and neutralizes HIV-1 strains from subtypes A, B, C, A/E, and G in a CD4-dependent manner. In the present study, we constructed glycosylphosphatidylinositol (GPI)-anchored VHH JM2 and JM4 along with an E4 control and transduced them into human CD4(+) cell lines and primary CD4 T cells. We report that by genetically linking the VHHs with a GPI attachment signal, VHHs are targeted to the lipid rafts of the plasma membranes. Expression of GPI-VHH JM4, but not GPI-VHH E4 and JM2, on the surface of transduced TZM.bl cells potently neutralizes multiple subtypes of HIV-1 isolates, including tier 2 or 3 strains, transmitted founders, quasispecies, and soluble single domain antibody (sdAb) JM4-resistant viruses. Moreover, transduction of CEMss-CCR5 cells with GPI-VHH JM4, but not with GPI-VHH E4, confers resistance to both cell-free and T cell-T cell transmission of HIV-1 and HIV-1 envelope-mediated fusion. Finally, GPI-VHH JM4-transduced human primary CD4 T cells efficiently resist both cell-free and T cell-T cell transmission of HIV-1. Thus, we conclude that VHH JM4, when targeted to the lipid rafts of the plasma membrane, efficiently neutralizes HIV-1 infection via both cell-free and T cell-T cell transmission. Our findings should have important implications for GPI-anchored antibody-based therapy against HIV-1. IMPORTANCE Lipid rafts are specialized dynamic microdomains of the plasma membrane and have been shown to be gateways for HIV-1 budding as well as entry into T cells and macrophages. In nature, many glycosylphosphatidylinositol (GPI)-anchored proteins localize in the lipid rafts. In the present study, we developed GPI-anchored variable regions (VHHs) of two heavy chain-only antibodies, JM2 and JM4, from immunized llamas. We show that by genetically linking the VHHs with a GPI attachment signal, VHHs are targeted to the lipid rafts of the plasma membranes. GPI-VHH JM4, but not GPI-VHH JM2, in transduced CD4(+) cell lines and human primary CD4 T cells not only efficiently blocks diverse HIV-1 strains, including tier 2 or 3 strains, transmitted founders, quasispecies, and soluble sdAb JM4-resistant strains, but also efficiently interferes T cell-T cell transmissions of HIV-1 and HIV-1 envelope-mediated fusion. Our findings should have important implications in GPI-anchored antibody-based therapy against HIV-1.